INFORMATION SERVICES ABOUT BIOGRAPHIES OF SUCCESSFUL FIGURES ON LEARNING INTEREST OF NINTH GRADE STUDENTS IN JUNIOR HIGH SCHOOL - Ayuningtyas, Ega; Sutja, Akmal; Zubaidah, Zubaidah (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
The main research focus is the low learning enthusiasm of ninth grade students at junior high school. This can be seen from various behaviors shown during the teaching and learning process, such as delayed learning, difficulty maintaining concentration, engaging in conversations with peers, and daydreaming. In addition, students tend to be less active in both individual and group learning sessions. The purpose of this study is to explore how biographical information services provided by successful individuals can affect students’ interest in learning. The research design used in this study is pre-experimental, specifically using a one group pretest-posttest approach. The sample size of this study consisted of 33 ninth grade students of junior high school. Through the research findings, the calculated T value is 5.525. Furthermore, the Sig (2-tailed) value of 0.05 corresponds to the two-sided T table value of 2.042. Notably, the calculated T value exceeds the T table value, indicating a large difference between the results before and after the application of biographical information services for successful individuals. After careful examination of the decision-making process and acceptance criteria, it was determined that Ha was accepted and Ho was rejected. In conclusion, the utilization of biographical information services for successful individuals has a significant impact on increasing students’ interest in learning.